Development of assessments in L2 Spanish during study abroad. (2nd July 2016) - Shively, Rachel L.
ABSTRACT: This study examines the development of speaker and listener assessments by second language (L2) learners of Spanish during a semester abroad in Spain. Assessments express the speaker's judgment, attitude, or affect towards what is said and perform the crucial functions of closing a topic and displaying shared understanding with an interlocutor. The results indicate that learners increased their use of listener assessments, as well as their use of specific structures and lexical items in speaker assessments. Participation in everyday conversation as well as explicit instruction represented ways that students could learn to make assessments. The article concludes with suggestions for teaching assessments in the Spanish L2 classroom.